Water availability controls nitrogen fixation in the feather moss, Pleurozium schreberi - Martin Ortega, Pablo (2008)
The influence of water availability in terms of amount and frequency of addition on N fixation of the feather moss Pleurozium schreberi was evaluated in a greenhouse experiment. Moss was collected in the Vaksliden forest reserve, northern Sweden, and subjected to several watering treatments. Three volumes of estimated monthly rainfall, low (20 L/ m2month), medium (60 L/m2month) and high (100 L/m2month) where each applied at three different frequencies, infrequently (every 15 days), medium frequency (every 5 days) and frequently (every day). As a general trend, N fixation was reduced when low volumes of water were applied and increased with medium and high water volumes. The increase in N fixation was related not only to the amount of water, but how frequently this water was added. As such, N fixation decreased as the interval between consecutive watering events was increased. The effect of the watering regime in the release of inorganic N (NO3--N, NH4+-N) and P (PO43--P) through the moss layer was measured by installing resin capsules under the moss layer. Overall, these nutrients were released in higher amounts when medium and high volumes of water were added except in the case of NO3--N. NO3--N which is highly soluble was found in higher amounts than any other nutrient, favored by the addition of low volumes of water. The release of NH4+-N was higher when the moss layer was subjected to infrequent watering. Although water availability was found to be an important factor controlling N fixation in P. schreberi, its role in the leakage of N as a source to the ecosystem remains to be investigated.